Rockwood & Wilkins' fractures in children - Flynn, John M.; Skaggs, David L.; Waters, Peter M. (Wolters Kluwer Health, 2015)
"For the gold-standard resource on pediatric fractures, reach for Rockwood and Wilkins' Fractures in Children. Written by leading orthopaedic surgeons from around the world, the revised and expanded 8th edition of this classic bestselling text presents complete, up-to-date coverage of all types of children's fractures. A must-read for pediatric orthopedic surgeons and orthopedic residents. Features: NEW expanded coverage of pain medicine and casting; NEW 6 new authors from around the world; NEW time-saving outline template for easy quick-reference. Step-by-step instructions and expert guidance on numerous operative and management techniques. Author's Preferred Technique section includes algorithms explaining why the author chose that procedure. Pearls and Pitfalls and preventive measures listed for all procedures. NEW 13 full length procedural videos. Casting, remodeling and unique features of children's fractures. Now with the print edition, enjoy the bundled interactive eBook edition, offering tablet, smartphone, or online access to: Complete content with enhanced navigation, A powerful search that pulls results from content in the book, your notes, and even the web, Cross-linked pages, references, and more for easy navigation, Highlighting tool for easier reference of key content throughout the text, Ability to take and share notes with friends and colleagues, Quick reference tabbing to save your favorite content for future use, 13 full length procedural videos"--Provided by publisher.